2020
DOI: 10.30658/hmc.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Sharing Stress With a Robot: What Would a Robot Say?

Abstract: With the prevalence of mental health problems today, designing human-robot interaction for mental health intervention is not only possible, but critical. The current experiment examined how three types of robot disclosure (emotional, technical, and by-proxy) affect robot perception and human disclosure behavior during a stress-sharing activity. Emotional robot disclosure resulted in the lowest robot perceived safety.Post-hoc analysis revealed that increased perceived stress predicted reduced human disclosure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The study reported that a social robot (NAO, SoftBank Robotics, see Figure 1) was successful in eliciting rich disclosures from human users, evidenced in the information that was shared, people's vocal output, and their perceptions of the interaction (34). This is in line with additional works that report different behavioral and emotional effects when communicating with social robots, and increased willingness of participants to disclose information and emotions in the presence of embodied artificial agents (e.g., 63,65,[88][89][90][91]. While participants were aware of many of the obvious differences between speaking to a humanoid social robot (NAO, SoftBank Robotics) compared to a disembodied conversational agent (Google Nest Mini voice assistant), their verbal disclosures to both were similar in length and duration (34).…”
Section: Overcoming Social Barrierssupporting
confidence: 72%
See 1 more Smart Citation
“…The study reported that a social robot (NAO, SoftBank Robotics, see Figure 1) was successful in eliciting rich disclosures from human users, evidenced in the information that was shared, people's vocal output, and their perceptions of the interaction (34). This is in line with additional works that report different behavioral and emotional effects when communicating with social robots, and increased willingness of participants to disclose information and emotions in the presence of embodied artificial agents (e.g., 63,65,[88][89][90][91]. While participants were aware of many of the obvious differences between speaking to a humanoid social robot (NAO, SoftBank Robotics) compared to a disembodied conversational agent (Google Nest Mini voice assistant), their verbal disclosures to both were similar in length and duration (34).…”
Section: Overcoming Social Barrierssupporting
confidence: 72%
“…It is important to highlight that while there is vast evidence in the social robotics and human-robot interaction research literature for the effect of social robots on human's behavior in health settings (e.g., 28,29,61), and on self-disclosure in particular (34,(62)(63)(64)(65)(66), eliciting information from trauma survivors (especially regarding the trauma and the associated affect) is substantially different and will impose different and new challenges. This will require further investigation via future empirical research, as it is vital to understand disclosure to a social robot (and how different it is from disclosure to a human or disembodied technologies) when people are in a hypervulnerable state.…”
Section: Supporting Early Diagnosis In Emergency Departmentsmentioning
confidence: 99%
“…ref. [20,[54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]); however, evidence is limited regarding how people's subjective perceptions of self-disclosure align with objective measures of self-disclosure. Here we evaluate both people's perceptions and their actual disclosures across three experiments.…”
Section: Subjective and Objective Disclosurementioning
confidence: 99%
“…ref. [8,9,[16][17][18][19][20][21]). Autonomous systems such as social robots can support care recipients in a variety of ways but also support their caregivers' physical and mental health (see ref.…”
Section: Introductionmentioning
confidence: 99%
“…In mass customization research, there is a large body of evidence that says when consumers participate in the co-creation of products, they like and value the products more (Atakan et al, 2014;Ling & Björling, 2020;Norton et al, 2012). Specifically, Franke et al (2010) show that the products designed by the users themselves produce feelings of accomplishment and ownership, resulting in the greater subjective value of the product.…”
Section: The Added Value Of Customizationmentioning
confidence: 99%